Interpretasi Sebaran Air Lindi Dengan Metode Potensial Diri dan Dampak Sosial Lingkungan di Kawasan Tempat Pembuangan Akhir (TPA) Kota Palangka Raya - Dwinanda, Indah Gumilang; Thareq, Subhan Ilham; Kurniati, Ety; Adelia, Kadek Ayu Cintya (Jurnal Pendidikan Fisika FKIP UM Metro, 2025)
Waste is one of the national problems that will have a direct impact on the environment and social in the community. In Indonesia itself, the open-dumping system is still the system applied in most landfills in Indonesia. The system is relatively simple and easy, but it is not free from many shortcomings, namely the emergence of leachate flows, especially in provinces/regions that have a dense population. The shortcomings of the system give urgency to the research conducted, namely analyzing and evaluating the distribution of leachate water in the Palangka Raya City Landfill using the self-potential method, especially with a fixed-based configuration. The purpose of this research is to analyze the potential difference value and its relationship to leachate flow, make a map of leachate distribution and flow and analyze the social environmental impact around the Palangka Raya City Landfill. The results showed that the anomalous distribution was blue to purple with a range of values around -4mV to -12 mV, a low potential difference value that can be interpreted as an accumulation of fluid flow or leachate below. Based on the results of data processing in the field, this shows that the distribution of anomalies with low values is on the side that leans closer to the garbage and away from residential areas. The water flow flows from the southwest to the northeast. The accumulation of fluid flow is also trapped in an area that is lower than its surroundings